PELAKSANAAN PRAKTEK KERJA INDUSTRI SISWA SMK PROGRAM KEAHLIAN TEKNIK BANGUNAN DI KOTA MAKASSAR - Anas Arfandi (LPMPP Universitas Negeri Yogyakarta, 2009)
AbstractThis study aimed to: (1) investigate the readiness of Vocational High School(VHS) students, the schools, and the industry to implement the industrialpracticum, (2) describe the implementation of the industrial practicum, and (3)describe the result of the industrial practicum implementation. This study was anevaluation research study using the Countenance Model. The research populationcomprised all teachers and principals of VHSs, all the industrial practicuminstructors, and all Year III VHS students of the building engineering expertiseprogram in Makassar City. The sample was selected using the proportionatestratified random sampling technique. The results showed that VHS students wereready to carry out the industrial practicum. This was supported by theirknowledge, basic skills and ability and socialization by the schools. VHSs wereready to implement the industrial practicum. Large- and middle-scale industrieswere ready to implement the industrial practicum. However, only 75% of smallscaleindustries were ready to do so. Cooperation between industries, especiallysmall ones, and vocational schools was less satisfactory. A few middle- and largescaleindustries, on the other hand, were quite good. The students activities in theindustrial practicum ran well because they were supported by their ability to adaptthemselves with the industrial environment. Their basic practical skills were poor.The teachers were also good, indicated by the intensity of their visits to theindustries during the industrial practicum. Such visits improved the studentsmotivation and supported them. The instructors also performed the activities well,especially in guiding the students during the industrial practicum. The instructorscontinuously provided guidance to the students before accomplishing assignmentsand checked the results. The final assessment by the instructors included studentsattendance, discipline, motivation, work quality, initiative, creativity, attitudes, andperformance. In the final achievement, most students were in the very satisfactorycategory and only a few were in the moderate category.Keywords: program evaluation, industrial practicum